Stool processing methods for Xpert Ultra testing in childhood tuberculosis: a prospective, multicountry accuracy study - Jaganath, Devan; Nabeta, Pamela; Nicol, Mark P; Castro, Robert; Wambi, Peter; Zar, Heather J; Workman, Lesley; Lodha, Rakesh; Singh, Urvashi B; Bavdekar, Ashish; Sanghavi, Sonali; Trollip, André; et al. (Clinical infectious diseases, 2025)
Centrifuge-free processing methods support stool Xpert Ultra testing for childhood tuberculosis, but data on their accuracy, acceptability, and usability are limited.We conducted a prospective evaluation of stool Xpert Ultra in India, South Africa, and Uganda with 3 methods: the Stool Processing Kit (SPK), the Simple One-Step method (SOS), and the Optimized Sucrose Flotation method (OSF). Children <15 years old with presumptive tuberculosis underwent sputum testing with Xpert Ultra and culture. We compared the accuracy of each method against a microbiological reference standard (tuberculosis if Xpert Ultra or culture positive) and a composite reference standard (tuberculosis if confirmed or unconfirmed tuberculosis). We surveyed laboratory staff to assess the acceptability and usability of the methods.We included 607 children, with a median age of 3.5 years (interquartile range, 1.3-7 years); 15.5% were human immunodeficiency virus positive. Against the microbiological reference standard, the sensitivities of SPK, SOS, and OSF were 36.9% (95% confidence interval, 28.6%-45.8%), 38.6% (17.2%-51.0%), and 31.3% (20.2%-44.1%), respectively, and the specificities, 98.2% (96.4%-99.3%), 97.3% (93.7%-99.1%), and 97.1% (93.3%-99%). The methods were acceptable and usable, but SOS was reported as most feasible to implement in a peripheral facility. Across methods, sensitivities increased among children who were culture positive (range, 55.0%-77.3%) and were low (13%-16.7%) against the composite reference standard. Adding stool Xpert Ultra increased sensitivity from 0% (OSF) to 11.8% (SPK/SOS), compared with sputum alone.Stool processing methods for Xpert Ultra were acceptable and usable and performed similarly, with highest sensitivity among children with culture-positive tuberculosis.
Gesehen am 16.12.2025